(untitled) - Keene, Donald (Tokyo, 1978)
The private recollections of long-time Japan resident, capture the personalities of certain Japanese people - some famous, some unknown - with insight and humour.
Keywords: Japanese literature,Authors, Japanese; History and criticism,Authors, Japanese; Biography